Notomicrus petrareptans sp. n., a new seep-dwelling species of Noteridae from Suriname (Coleoptera: Adephaga) - Baca, Stephen M.; Short, Andrew Edward Z. (Zootaxa, 2018)
Notomicrus petrareptans sp. n. is described from an inselberg seepage in southwestern Suriname. This species is diagnosable by a combination of its weakly punctate elytra, respective shapes of the pro- and mesotarsal claws (males), and long and slender median lobe of the aedeagus. This is the first member of the subfamily Notomicrinae to be described from hygropetric seep habitats and only the second known seep-dwelling species of the family Noteridae. Diagnostic characters are illustrated and habitat images are provided.